External Parasites of Poultry - Phillip E. Kaufman; Philip G. Koehler; Jerry F. Butler (EDIS)
Arthropods are important pests of poultry in Florida, especially where proper management practices are not implemented. Lice and mites are the most common pests of poultry in Florida although the fowl tick and the sticktight flea may also cause serious problems. Though not a parasite of poultry, the house fly is a major concern to poultry producers, especially in caged-layer operations. This document is ENY-290 (IG140), one of a series of the Entomology and Nematology Department, UF/IFAS Extension. Original publication date July 1977. Revised March 2006.